Evaluation of Feeding Effects of A1 and A2 Cow Milk-Based Diet on Hematological Parameters in Obese Mice Model - , Preeti; Mukesh, Manishi; Singh, Pamela; Amarjeet; Dubey, Shivam Kumar; Chaudhary, Vipul; kataria, R S; Niranjan, Saket Kumar; Mohanty, Ashok Kumar; Sodhi , Monika (The Indian Journal of Animal Reproduction, 2025)
Beta-casein is one of the four caseins that make up approximately 80% of cow’s milk proteins. Of the 15 known genetic variants of β-casein, A1 and A2 are the most prevalent. These two variants differ by a single amino acid at position 67, where the A2 variant contains proline, while in the A1 variant, proline is replaced by histidine. Based on A1 and A2 β-casein variants cow milk is categorized as A1 and A2 milk receptively. Structural variations due to change of amino acid result in generation of different bioactive peptides during gastrointestinal protease digestion and beta casomorphin 7 (BCM-7) released from digestion of A1 milk has been implicated as risk factor for human health. In the present study, we analyzed the effect of A1/A2 milk powder-based diet on hematological parameters in obese model of C57BL/6J mice (fed with high-fat diet). Mice in different diet groups were fed with milk powder-based diet prepared from milk with three different genotypes (A1A1, A1A2 and A2A2) with reference to A1/A2 allele of beta casein for 90 days. The observations revealed significant changes in blood glucose, Hb, HCT, WBC and RBC count in mice from control vis a vis high fat diet group. HFD+A1A1/A1A2 group also showed significant alterations in blood glucose changes compared to control. Across the milk powder-based diet groups, blood glucose level and WBC count in HFD+A1A1 group was significantly higher than HFD+A2A2 group pointing towards the potential pro-inflammatory response. No changes were observed in Hb, hematocrit, MCV or RBC count across milk powder-based diet groups. However, this is a preliminary study that would need further exploration.